Functioning of transnational law enforcement to ensure social guarantees for the Ukrainian community in the United States - Fursenko, Nataliia (Український політико-правовий дискурс, 2026)
The relevance of the study is determined by the intensification of migration processes caused by Russia’s full-scale aggression against Ukraine, which has significantly increased the Ukrainian community in the U.S. and actualized the problem of ensuring social guarantees in a transnational legal environment. Under such conditions, law enforcement extends beyond national jurisdictions, which necessitates a rethinking of mechanisms for ensuring social protection within the interaction of different legal systems. The purpose of the article is to substantiate the theoretical and applied foundations of the functioning of transnational law enforcement mechanisms in ensuring social guarantees for the Ukrainian community in the U.S. – taking into account the interaction of legal systems and institutional mechanisms. The methodological basis of the research is formed by comparative legal analysis, systemic and structural-functional approaches, methods of institutional analysis, as well as elements of empirical generalization of administrative practice. Results. It has been studied that transnational law enforcement in the field of social protection operates as a multi-level system based on the interaction of normative, institutional, and adaptive components. It has been revealed that the effectiveness of such mechanisms depends on the degree of coherence between legal norms, administrative procedures, and institutional coordination. It has been proven that fragmentation of legal regulation, absence of coordinated social security mechanisms, and territorial variability of implementation practices significantly limit access to social guarantees for the Ukrainian community in the U.S. It has been established that procedural complexity, informational asymmetry, and insufficient interoperability of administrative systems create barriers to the practical realization of formally guaranteed rights. Conclusions. It has been substantiated that improving effectiveness requires strengthening intersystem coordination, standardizing administrative procedures, expanding access to legal assistance, and developing coordinated approaches to social security, including the recognition of insurance periods. It has been concluded that transnational law enforcement should be oriented toward long-term sustainability rather than short-term adaptive responses. Prospects for further research are associated with the development of integrated models for assessing the effectiveness of transnational law enforcement mechanisms and with the design of legal instruments ensuring continuity of social rights in cross-border contexts.